Coping with the Loss of Pooling Synergy in Cellular Manufacturing Systems - Suresh, Nallan C.; Meredith, Jack R. (Management Science, 1994)
The conversion of a functional layout into a cellular manufacturing system involves the partitioning of several multiserver work centers. The loss of pooling synergy in this process can be significant, and this paper investigates the impact of several measures to overcome the adverse effects on flow time, work-in-process inventory and machine utilization. These can be alleviated to a certain extent through reductions in setup times and lot sizes that has been traditionally emphasized in group technology, but a more concerted effort is required. Analytical models are first utilized to investigate the extent to which these adverse effects can be overcome through (1) reduction in setup time, (2) lot sizing, (3) reduction in the variability of process-times and job arrivals, and, (4) reduction in processing times through productivity improvements, all arising from part family-oriented processing. These insights are verified through a simulation comparison of five cellular manufacturing systems with a functional layout system in which optimal lot sizes, low move times and a part family-oriented scheduling rule are used.